(untitled) (Current Horticulture, 2024)
The study was carried out on fresh, one, two and three year aged seeds of guava (Psidium guajava L. ) L-49 (Sardar) in the laboratoryof Department of Seed Science and Technology, CCS HAU, Hisar, during 2018-2019. The seeds were subjected to different seed scarification treatments, viz. hot water treatment at 80°C for 1 minute, concentrated sulphuric acid for quick dip and water soaking for 48 hr. The seeds were assessed for peroxidase activity, dehydrogenase activity and electrical conductivity. Hot water treatment at 80°C for 1 minute resulted into maximum peroxidase activity (710.0) and dehydrogenase activity (0.233) but minimum electrical conductivity (11.02). It is concluded that seeds treated with hot water treatment at 80°C for 1 minute showed maximum peroxidase, dehydrogenase activities and minimum electrical conductivity which reflects that better seed quality.